Unlocking New Methods to Estimate Country-Specific Trade Costs and Trade Elasticities - Rebecca Freeman; Mario Larch; Angelos Theodorakopoulos; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2021)
We propose new methods to identify the full impact of country-specific characteristics on bilateral trade flows within the framework of `the new quantitative trade model.' We complement theory with a simple two-stage estimating procedure, and offer a proof of concept by quantifying the impact of country-specific R&D expenditure on trade. Results suggest a positive relationship overall, but a larger impact on international (versus domestic) trade. Further, our methodology allows us to recover trade elasticity estimates without the need for price/tariff data. Bringing this to the sectoral level, we obtain estimates of the trade elasticity for manufacturing, services, and tradable versus non-tradable sectors.
Keywords: F10; F14; F16; 330; structural gravity; country-specific trade costs; trade elasticity; elasticity of substitution; R&D and trade